Bases of methodology of an estimation of influence on an environment of water-economic objects - V. L. Bondarenko; V. V. Gutenev; V. V. Privalenko; S. G. Prygunov; A. I. Azhgirevich (Юг России: экология, развитие)
Methodological bases of the estimation of the influence on the environment (EIE) of the water resources formation are considered in the article.